A Study on IOT based smart Irrigation System & Weather forecasting Using ESP 8266 - P. K. Sheela Shanthakumari, K. Mahalakshmi, J. Senthil Murugan, W. T. Chembian, Tharun R, Vishal Krishnan R, Yameen Ali J (Mathematical Statistician and Engineering Applications, 2023)
In recent Days Dense farming usually consumes a lot of resources formaintenanceis required.The grow task is based on time frequency, not actual plantneeds.Also,thedisadvantages,weather in conditions such as too cold temperatures orhumidityabovesupportedvaluesif you don't control it in time, it will damage your crops. Allthesetasksareevenharder tomaintainConquer large areas.(IOT) based system to monitor the crop’s health by monitoring the following factors such as: Temperature, Humidity and Soil Moisture and all the live data can be viewed in single application. A surveillance automation system mayhelpFarmers warn them when predetermined conditions are met.Withsomething moreIntegration can also enable some electronic controls,includingweighing machines’ Measures to secure the harvest. This project aims to create acompletelyopen sourceand complete.Collectdatafromthefieldusing(IoT)architecture;Send them to a central server. You can use the ESP8266 PicoWboard, is more accurate and efficientcomparedtoothermicrocontrollerboard. By using this IOT system and AI software the crop health can be tracked, monitored, crop field can be watered and also any doubts or problems faced by farmers regarding agriculture can be solved.